Differentiation of Amaranthus Species and Estimation of Their Polyphenolic Compounds and Antioxidant Potential Using Near-Infrared Spectroscopy - Svetoslava Terzieva; Neli Grozeva; Milena Tzanova; Petya Veleva; Mariya Gerdzhikova; Stefka Atanassova (Plants)
Amaranthus species are rich in protein, fiber, minerals, and other nutrients and have various health benefits. The genus is taxonomically difficult due to the high phenotypic plasticity and the spontaneous interspecies introgression and hybridization between species. The purpose of this study is to evaluate the possibilities of near-infrared spectroscopy (NIRS) for the taxonomic differentiation of some of the species common in Bulgaria and estimate their polyphenolic compounds. Tested samples were collected from six Bulgarian floristic regions: Amaranthus albus L., A. blitum L., A. deflexus L., A. hybridus L., and A. retroflexus L. were studied. The NIR spectra of dried and ground leaf and stalk samples were measured by NIRQuest 512 (region 900–1700 nm) using a fiber-optic probe. Soft independent modeling of class analogy (SIMCA) was used to develop the classification models and PLS regression for the quantitative determination of their polyphenolic compounds and antioxidant potential. There were statistically significant differences in the measured values of polyphenolic compounds and antioxidant potential among the tested species. NIRS allowed an accurate determination of these parameters. The performance of developed SIMCA models for the discrimination of species was very high. The precision of determination varied from 98.2 to 100%, and the total accuracy was 98.34%. The results show successful differentiation of the taxonomic species.